2020
DOI: 10.5194/nhess-20-1321-2020
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate statistical method for susceptibility analysis of debris flow in southwestern China

Abstract: Abstract. Southwestern China is characterized by many steep mountains and deep valleys due to the uplift activity of the Tibetan Plateau. The 2008 Wenchuan earthquake left large amounts of loose materials in this area, making it a severe disaster zone in terms of debris flow. Susceptibility is a significant factor of debris flows for evaluating their formation and impact. Therefore, there is an urgent need to analyze the susceptibility to debris flows of this area. To quantitatively predict the susceptibility … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…However, it is difficult to obtain this information in a sparsely-populated alpine area, so available secondary factors that can characterize the scale and frequency of debris flows can be adopted. They can be used in combination with primary factors to constitute a multi-factor assessment model (Ji et al, 2020). The spreading area has been calculated by the Flow-R model, from which the following eight factors can be extracted to establish a rapid assessment method.…”
Section: Determination and Quantification Of Assessment Factorsmentioning
confidence: 99%
“…However, it is difficult to obtain this information in a sparsely-populated alpine area, so available secondary factors that can characterize the scale and frequency of debris flows can be adopted. They can be used in combination with primary factors to constitute a multi-factor assessment model (Ji et al, 2020). The spreading area has been calculated by the Flow-R model, from which the following eight factors can be extracted to establish a rapid assessment method.…”
Section: Determination and Quantification Of Assessment Factorsmentioning
confidence: 99%
“…The landslide intensity (simulation volume) (y 1 ), debris flow intensity (peak discharge (y 2 ) and velocity (y 3 ), altitude (y 4 ), relief degree (y 5 ), degree of basin cutting (y 6 ), lithology (y 7 ), distance to the fault (y 8 ), NDVI (y 9 ), FVC (y 10 ), soil erosion (y 11 ), water erosion (y 12 ), and human activity index (y 13 ) were selected as the hazard factors for the debris flow and were divided into five levels according to different thresholds and were assigned values of 0.2, 0.4, 0.6, 0.8, or 1.0. w is the weight of each factor, which was synthesized using the Entropy Method (EM) and the Analytic Hierarchy Process (AHP) which need to refer to the explanation of factor weight in the existing research [61][62][63][64].…”
Section: Hazard Assessment Of Seismic Landslide-generated Debris Flowmentioning
confidence: 99%
“…The results show that the risks posed by landslides in high earthquake intensity areas may be lower than those in low earthquake intensity areas, which may be related to the influence of the regional geological conditions and the errors in the existing earthquake-landslide hazard assessments [41,74]. In view of the uncertainty of regional risk results, factor analysis methods can be further used to explore the sensitivity of risks to topography, environment, and other factors to further clarify the characteristics of disaster chain risks [63,64,75]. In summary, it would be valuable to collect more disaster data, strengthen field investigations, and improve research on mechanism processes and verify the simulation results from multiple aspects [63,64,75].…”
Section: Reliability Of Population Risk For the Disaster Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that this relation significantly improves the perdition of extremes, with 30 % exhibiting their non-linear relationship with climate mechanisms. Kudryavtseva et al (2021) assessed the non-stationarity of extreme water levels in the eastern Baltic Sea with a particular focus on the Gulf of Riga. The analysis uses tide gauge observations from 1961 to 2018 and the block maxima method to identify extreme events.…”
mentioning
confidence: 99%